Dinamika Pola Komunikasi Keluarga pada Mahasiswa Perantauan - Risma Khoirunnisa; Elda Putri Azkiya; Mia Rusmiati; Solihat Suci Ayutriani; Nabila Kinantia; Nasya Aulia Khairunada; Yani Achdiani; Sarah Nurul Fatimah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to analyze the dynamics of family communication patterns in overseas students, especially the relationship between students and parents who are influenced by physical distance and time differences. The method used is descriptive qualitative with a literature study approach that collects and analyzes various literature related to family communication and the challenges of long-distance communication. The results of the study show that effective, open, and consistent family communication patterns are very important in maintaining relationship harmony and psychological support for overseas students. Communication technologies such as social media, WhatsApp, and video calls play a major role in bridging distance limitations, although technical barriers and busy activities are often the main challenges. Adaptation strategies such as scheduling communication time and developing interpersonal communication skills are important solutions to overcome these obstacles. Honest and open communication can strengthen emotional bonds, reduce stress, and increase students' motivation to learn and academic success. Conversely, ineffective communication can potentially lead to emotional isolation and decreased mental well-being. This research confirms that the establishment of healthy and supportive communication patterns between overseas students and their families is crucial to support students' personal and academic development.